A Comparison of mango kernel starch with a novel starch from litchi (Litchi chinensis) kernel: Physicochemical, morphological, pasting, and rheological properties. Issue 4 (3rd April 2017) - Thory, Rahul; Sandhu, Kawaljit Singh
ABSTRACT: A novel starch was isolated from litchi kernel and compared with mango kernel starch. The properties studies were physicochemical, morphological, pasting, rheological, X-ray diffraction, and morphological. Litchi kernel starch had significantly ( p < 0.05) higher amylose content and solubility, whereas its swelling power and paste clarity were lower than mango kernel starch. Peak viscosity and breakdown viscosity of litchi kernel starch were lower than mango kernel starch; however, it showed higher setback viscosity. The scanning electron microscopy revealed the presence of starch granules varying in size and shape from small to large and oval to elliptical, respectively, in litchi kernel starch. The mean length of small and large litchi starch granules was 9.52 and 50 µm, respectively, while the mean breadth of small and large litchi starch granules was 7.14 and 35.7 µm, respectively. X-ray diffractions of both litchi and mango kernel starches showed typical A-type patterns. During heating, litchi kernel starch showed higher peak G' (storage modulus), G'' (loss modulus), and breakdown in G' in comparison to mango kernel starch. The peak tan δ of litchi and mango kernel starch was <1, which indicated that both litchi and mango kernel starches were more elastic than viscous.